Micropropagation of recalcitrant pine (Pinus pinea L) an overview of the effects of ectomycorrhizal inoculation - Ragonezi, Carla (2012)
Oral presentation Micropropagation of recalcitrant pine (Pinus pinea L.). An overview of the effects of ectomycorrhizal inoculation Carla Ragonezi1; Ana Teresa Caldeira2 3; Maria do Rosário Martins2,5; Otília Miralto5,6; Luís Silva Dias6; Elsa Ganhão6, Krystyna Klimaszewska4, Amely Zavattieri5,6 1 Plant Breeding and Biotechnology Laboratory, University of Évora, Ap. 94, 7002-554 Évora, Portugal 2 Department of Chemistry, University of Évora, Ap. 94, 7002-554 Évora, Portugal 3 CQE, University of Évora, Rua Romão Ramalho, nº 59, 7000-671 Évora, Portugal 4 Natural Resources Canada, Canadian Forest Service, Laurentian Forestry Centre, 1055 du P.E.P.S., P.O. Box 10380, Stn. Sainte-Foy, Québec, QC G1V 4C7, Canada 5 ICAAM, University of Évora, Ap. 94, 7002-554 Évora, Portugal 6 Department of Biology, University of Évora, Ap. 94, 7002-554 Évora, Portugal Corresponding author: Carla Ragonezi email: cazi04@yahoo.com.br Abstract Stone pine (Pinus pinea L.) is an economically important forest species in some regions of Iberian Peninsula. Portugal and Spain have nearly 500,000 ha of stone pine stands, representing 85% of worldwide distribution. The main utilization of this species is for the production of seeds (pinion) for food industry. In addition to its enormous profitability as a producer of seeds, it has beneficial impact on soil protection, dunes fixation and also it is a pioneer species particularly for cork and holm oaks degraded ecosystems. The stone pine plantations are today a major source of income for forestry holdings. The investments have targeted breeding, reforestation, forest management and harvesting. The maternal inheritance of desirable characteristics such as cone weight, number of seeds per cone and seed length is considerably high in this species thus encouraging the selection of seeds from “plus” trees. The select trees have been propagated by grafting and micropropagation. However, grafting generates high variability due to scion-rootstock interaction that varies production levels. The production of clonal plants from selected seeds by micropropagation techniques has advanced very slowly due to the recalcitrance of this species in tissue culture and particularly to adventitious rooting of microshoots. Due to the tremendous importance of developing a reproducible tissue culture method for clonal propagation, a study has been carried out for over a decade to enhance rooting and acclimation. During this period of time, continuous increments in the multiplication rate and rooting frequency were achieved by introducing variations in culture media composition and conditions. Auxins, carbohydrates, light (both quality and duration) and temperature were used at different concentrations and levels as well as compounds such as coumarine; salicylic acid, polyamines, etc were tested for induction and expression phases of adventitious rooting. Despite these efforts, the microshoots regenerated through organogenesis from mature embryo cotyledons failed to root or to have sustained root growth. At this point, an in vitro co-culture technique of stone pine microshoots with ectomycorrhizal-fungi was introduced to overcome the adventitious root growth cessation in vitro and to improve root development during acclimation phase. An overview of the results showing the positive effect of fungal inoculation in promoting root growth in vitro and on plantlet survival during acclimation will be presented. Preliminary results of biochemical signals detected between Pinus pinea/Pisolithus arhizus during early steps of in vitro culture by liquid chromatography-mass spectrometry that might be responsible for the positive effect on root growth will be also presented. Key words: acclimation, co-culture, ectomycorrhiza, in vitro adventitious rooting, micropropagation, stone pine.